A comparative life-cycle analysis of tall onshore steel wind-turbine towers. Issue 4 (25th November 2019) - Stavridou, N; Koltsakis, E; Baniotopoulos, C C
Abstract: Earth has lately been suffering from unforeseen catastrophic phenomena related to the consequences of the greenhouse effect. It is therefore essential not only that sustainability criteria be incorporated into the everyday lifestyle, but also that energy-saving procedures be enhanced. According to the number of wind farms installed annually, wind energy is among the most promising sustainable-energy sources. Taking into account the last statement for energy-saving methods, it is essential to value the contribution of wind energy not only in eliminating CO2 emissions when producing electricity from wind, but also in assessing the total environmental impact associated with the entire lifetime of all the processes related with this energy-production chain. In order to quantify such environmental impacts, life-cycle analysis (LCA) is performed. As a matter of fact, there are a very limited number of studies devoted to LCA of onshore wind-energy-converter supporting towers—a fact that constitutes a first-class opportunity to perform high-end research. In the present work, the life-cycle performance of two types of tall onshore wind-turbine towers has been investigated: a lattice tower and a tubular one. For comparison reasons, both tower configurations have been designed to sustain the same loads, although they have been manufactured by different production methods, different amounts of material were used and different mounting procedures have been applied; all the aforementioned items diversify in their overall life-cycle performance as well as their performance in all LCA phases examined separately. The life-cycle performance of the two different wind-turbine-tower systems is calculated with the use of efficient open LCA software and valuable conclusions have been drawn when combining structural and LCA results in terms of comparing alternative configurations of the supporting systems for wind-energy converters.